Tratamento de queloides usando radioterapia pósoperatória com elétrons: Estudo comparativo e randomizado com dois esquemas - de Oliveira Junior, Batista [UNESP]; Schellini, Silvana Artioli [UNESP]; Lastória, Joel Carlos [UNESP]; de Carvalho, Lídia Raquel [UNESP]; Stolf, Hamilton Ometto [UNESP]; de Oliveira, Ana Laura Paludetto (My University, 2013)
Introduction: While several keloid treatment modalities exist, they all offer disappointing results when performed in isolation. The combination of surgical excision and post-operative irradiation with electron beams is effective in improving the quality of scars and reducing the recurrence rate of the condition. Objective: To assess, on a comparative basis, the prospects for cure, and also side effects in the irradiated areas of two treatment methods using electron beams.Methods: A prospective, comparative and randomized clinical study was carried out at the Faculdade de Medicina de Botucatu-UNESP, in Botucatu (SP), Brazil, between 2008 and 2010. The study included patients who were post-operative after their treatment for the resection of keloids. The study population was divided into groups G1 and G2, having received radiotherapy treatment with electrons from a linear accelerator at 30 Gy/10 fractions and 32 Gy/16 fractions, respectively.The patients were followed up with for 18 months. Results were assessed through the observation of two independent evaluators and the distribution of a questionnaire to study participants. Results: Forty-three patients were investigated (21in G1 and 22 in G2). 52.4% showed good results in G1, with a recurrence rate of 47.6%. In G2, 91% showed good results, with a 9% recurrence rate. Conclusion: The 32 Gy/16 fractions method was proved to be superior to the 30 Gy/10 fractions method, resulting in a better therapeutic response and fewer side effects.
Keloid treatment using postoperative radiotherapy with electron beams: A comparative randomized study of two methods
Keywords: Electrons; Keloid; Radiotherapy